2011
DOI: 10.1111/j.1937-5956.2010.01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Advance Selling by a Newsvendor Retailer

Abstract: R etailers often face a newsvendor problem. Advance selling helps retailers to reduce demand uncertainty. Consumers, however, may prefer not to purchase in advance unless given a discount because they are uncertain about their valuation for the product in advance. It is then unclear whether or when advance selling to pass some uncertainty risk to consumers is optimal for the retailer. This paper examines the advance selling price and inventory decisions in a two-period setting, where the first period is the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
148
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(154 citation statements)
references
References 29 publications
4
148
2
Order By: Relevance
“…Swinney (2011) finds that when consumers learn their preferences over time, the value of quick-response production practices is generally diminished as a result of forward-looking consumer behavior. YU et al (2013a) and Prasad et al (2011) investigate whether and how retailers should employ advance selling to uninformed consumers. An exception to the exogenous revelation of preferences assumed in the above papers is Jing (2011), who considers a responsive pricing problem in which consumers are more likely to become informed about their preferences as the number of early adopters increases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Swinney (2011) finds that when consumers learn their preferences over time, the value of quick-response production practices is generally diminished as a result of forward-looking consumer behavior. YU et al (2013a) and Prasad et al (2011) investigate whether and how retailers should employ advance selling to uninformed consumers. An exception to the exogenous revelation of preferences assumed in the above papers is Jing (2011), who considers a responsive pricing problem in which consumers are more likely to become informed about their preferences as the number of early adopters increases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhao and Stecke () studied how a retailer should design the advance selling strategy taking consumer loss aversion into consideration. Prasad et al () studied a newsvendor problem in which a retailer sells with pre‐orders in the presence of heterogeneous consumers. They found that advance selling is not always beneficial to a retailer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Advance selling is a strategy in which consumers can buy new products (or services) with pre‐orders (Tian and Wang, ). This strategy has been proved effective because it can reduce demand uncertainty through advance information updating and generate more demand (Prasad et al, ; Zhao & Stecke, ; Zhao et al, ; Wei & Zhang, ). With the rapid development of e‐commerce, many industries have implemented an advance selling strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Domestic and foreign scholars for the Presale and Refunding issues such as the study, Xie [1] and Zhao [2] and others who studied the manufacturers when the presale and how to presale problems, and according to the consumer's risk aversion preferences put forward retail Businessmen do not provide presale, to provide a presale with a moderate discount and provide a deep discount of the presale three presale strategy in the consumer product valuation, Prasad [3], Zeng [6] and Li [7] And others believe that presale can help retailers reduce the uncertainty of demand, they will be the consumer's valuation of the product is divided into certainty and uncertainty, the study of the presale, normal sales and presale and then normal sales In the category of consumer types, Swinney [4] divides consumers into hyperopia consumers and myopia consumers, Nocke [5] that consumers can be divided into the valuation of products and low valuation of two Type .Lim [8] and others based on the market demand is known under the premise of the study with hyperopia consumers, myopia consumers and speculators of the presale market, and the presale market is divided into product appreciation market and product depreciation market , Found that the existence of speculators can give retailers a certain profit and in the presale stage speculators and hyperopia consumers purchase decision is consistent in the consumer returns, Wang Junping [9] and others online sales for easy online The problem of optimal ordering of supply chain is studied by a two-stage dynamic programming to describe the two order behaviors of online sellers in the dynamic market environment. In addition, both the presale and the consumer In the research of return problem, Li Yongjian [10] and Zhang Fuli [11] studied the presale strategy and the defect-free return of the newsboy retailer under the premise that the product demand and the consumer valuation were uncertain.…”
Section: Introductionmentioning
confidence: 99%